EXCHANGE RATE VOLATILITY, IMPORT, AND EXPORT PERFORMANCE IN FIVE ASEAN COUNTRIES A PANEL DATA ANALYSIS FROM A ISLAMIC ECONOMIC PERSPECTIVE (2000-2024): A PANEL DATA ANALYSIS FROM A ISLAMIC ECONOMIC PERSPECTIVE (2000-2024) - Alifia Putri Salsabila; Evi Ekawati; Taufiqur Rahman (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
The global economic crisis caused a decline in the value of the currencies of 5 ASEAN countries which had an impact on the volume of exports and imports. This research aims to analyze the relationship between exchange rate volatility and imports on exports in five ASEAN countries, namely Indonesia, Malaysia, Thailand, the Philippines, and Singapore, from an Islamic economic perspective. The research employs a quantitative approach using panel data covering the period from 2000 to 2024. Data analysis was conducted using Eviews software through the selection of the best model among the Common Effect, Fixed Effect, and Random Effect models, followed by Chow and Hausman tests. The results indicate that exchange rate volatility and imports have a positive and significant relationship with exports in the ASEAN region. These findings suggest that increased imports of capital goods and raw materials can stimulate export growth, while stable exchange rate conditions enhance the competitiveness of international trade. From an Islamic economic perspective, these results reflect the principles of justice and balance in cross-country economic activities.